1971
DOI: 10.1021/ma60020a005
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Ferrocenylmethyl Acrylate and Ferrocenylmethyl Methacrylate with Organic Monomers

Abstract: Two novel ferrocene-containing monomers, ferrocenylmethyl acrylate, la (FMA), and ferrocenylmethyl methacrylate, lb (FMMA), have been synthesized. Both la and lb were copolymerized with styrene, methyl acrylate, methyl methacrylate, and vinyl acetate in benzene solutions initiated by azobisisobutyronitrile (AIBN) at 70°. Homogeneous copolymers were formed in each case, and the relative reactivity ratios of each copolymerization were determined. The values of n and r2 were:FMA (monomer l)-styrene = 0.02, r2 = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Pittman et al reported homopolymerization of 2‐ferrocenylethyl acrylate and 2‐ferrocenylethyl methacrylate and the copolymerization 2‐ferrocenylethyl acrylate and methacrylate with styrene, methyl acrylate and methyl methacrylate. As shown in Scheme , both homo‐ and copolymerization were initiated by azobisisobutyronitrile (AIBN) in benzene or ethyl acetate solution at 60–80°C.…”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%
“…Pittman et al reported homopolymerization of 2‐ferrocenylethyl acrylate and 2‐ferrocenylethyl methacrylate and the copolymerization 2‐ferrocenylethyl acrylate and methacrylate with styrene, methyl acrylate and methyl methacrylate. As shown in Scheme , both homo‐ and copolymerization were initiated by azobisisobutyronitrile (AIBN) in benzene or ethyl acetate solution at 60–80°C.…”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%
“…Other ferrocene‐containing monomers such as methacrylate and acrylate have been shown to undergo radical polymerization . For example, Pittman and co‐workers demonstrated the feasibility of AIBN‐catalyzed, free radical homopolymerization of ferrocenylmethyl acrylate and ferrocenylmethyl methacrylate in benzene solution.…”
Section: Polymerization Of Sandwich Complex‐bearing Monomersmentioning
confidence: 99%
“…For example, poly(ferroceneylmethyl acrylate) had T g in the range of 197–210 °C that was significantly higher than that of poly(methyl acrylate) . The Pittman group also reported the AIBN‐catalyzed, free radical homopolymerization of 2‐ferrocenylethyl acrylate and 2‐ferrocenylethyl methacrylate as well as the copolymerization of these monomers with styrene, vinyl acetate, methyl acrylate, and methyl methacrylate (Scheme ) . The homopolymerizations of these monomers, which were also first order in [monomer] and half order in [AIBN], afforded high‐molecular‐weights polymers (M¯n = 14 700–82 300 g mol −1 ).…”
Section: Polymerization Of Sandwich Complex‐bearing Monomersmentioning
confidence: 99%
“…Petroleum ether (50 cm 3 ) was added drop-wise to the cooled mixture to precipitate the yellow copolymer, which was filtered, rinsed with a mixture of petroleum ether and benzene (2:1 volume) repeatedly and vacuumed to be dried. The ferrocenyl group was identified by UV-vis spectra of which specific band was at 435 nm [24].…”
Section: Synthesis Of Fcma/styrene Copolymermentioning
confidence: 99%